Trimethoxy‐Resveratrol and Piceatannol Administered Orally Suppress and Inhibit Tumor Formation and Growth in Prostate Cancer Xenografts. Issue 11 (8th May 2013) - Dias, Steven J.; Li, Kun; Rimando, Agnes M.; Dhar, Swati; Mizuno, Cassia S.; Penman, Alan D.; Levenson, Anait S.
Abstract BACKGROUND Resveratrol (Res) is recognized as a promising cancer chemoprevention dietary polyphenol with antioxidative, anti‐inflammatory, and anticancer properties. However, the role of its analogues in prostate cancer (PCa) chemoprevention is unknown. METHODS We synthesized several natural and synthetic analogues of Res and characterized their effects on PCa cells in vitro using a cell proliferation assay. A colony formation assay and in vitro validation of luciferase (Luc) activity was done for LNCaP‐Luc cells that were consequently used for in vivo studies. The efficacy of Res, trimethoxy‐resveratrol (3M‐Res) and piceatannol (PIC) was studied in a subcutaneous (s.c.) model of PCa using oral gavage. Tumor progression was monitored by traditional caliper and bioluminescent imaging. The levels of cytokines in serum were examined by ELISA, and the levels of compounds in serum and tumor tissues were determined by gas chromatography‐mass spectrometry. RESULTS We examined the anti‐proliferative activities of Res/analogues in three PCa cell lines. We further compared the chemopreventive effects of oral Res, 3M‐Res, and PIC in LNCaP‐Luc‐xenografts. We found that 2 weeks pretreatment with the compounds diminished cell colonization, reduced tumor volume, and decreased tumor growth in the xenografts. Both 3M‐Res and PIC demonstrated higher potency in inhibiting tumor progression compared to Res. Notably, 3M‐Res was the most active in inhibiting cell proliferation and suppressing colony formation, and its accumulation in both serum and tumor tissues was the highest. CONCLUSIONS Our findings offer strong pre‐clinical evidence for the utilization of dietary stilbenes, particularly 3M‐Res, as novel, potent, effective chemopreventive agents in PCa. Prostate 73: 1135–1146, 2013. © 2013 Wiley Periodicals, Inc.